2011
DOI: 10.1523/jneurosci.0504-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Darks Are Processed Faster Than Lights

Abstract: Recent physiological studies claim that Dark stimuli have access to greater neuronal resources than Light stimuli in early visual pathway. We used two sets of novel stimuli to examine the functional consequences of this Dark dominance in human observers. We show that increment and decrement thresholds are equal when controlled for adaptation and eye-movements. However, measurements for salience differences at high-contrasts show that Darks are detected pronouncedly faster and more accurately than Lights when p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
90
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(114 citation statements)
references
References 33 publications
19
90
5
Order By: Relevance
“…Furthermore, we show that the background luminance affects more ON than OFF channels in their response magnitude, response linearity, and receptive field size. Finally, we show that changes in the ON channel with background luminance can explain the dynamics of the irradiation illusion: The illusion is perceived stronger on dark/light backgrounds than on gray backgrounds (7).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Furthermore, we show that the background luminance affects more ON than OFF channels in their response magnitude, response linearity, and receptive field size. Finally, we show that changes in the ON channel with background luminance can explain the dynamics of the irradiation illusion: The illusion is perceived stronger on dark/light backgrounds than on gray backgrounds (7).…”
Section: Discussionmentioning
confidence: 77%
“…Galilei (4) related the difference in resolution to the observation that a light patch on a dark background appears larger than the same sized dark patch on a light background, an illusion that von Helmholtz (5) named the "irradiation illusion." Although this illusion has been studied in the past (6,7), its underlying neuronal mechanisms remain unknown. It has been suggested that the perceived size differences could be caused by the light scatter in the optics of the eye followed by a neuronal nonlinearity (6,7), but there are no neuronal measurements of a nonlinearity that fits the explanation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Such asymmetries in response to contrast polarity probably have their origin in an early compressive response to luminance, perhaps driven by local light adaptation at the photoreceptor level. Such a nonlinearity gives rise to polarity asymmetries in a great variety of perceptual outcomes (Lu & Sperling, 2012), including perceived size and perceived location of edges (Georgeson & Freeman, 1997;Mather & Morgan, 1986), and reaction times (Komban, Alonso, & Zaidi, 2011). It is also reflected in neural responses at the retinal, lateral geniculate and cortical levels (Kremkow et al, 2014).…”
Section: Resultmentioning
confidence: 99%
“…This finding is quite different from those in several previous studies that reported a general increase of response amplitude without changes of dynamics in V1 responses to small black vs. white stimuli. For instance, investigations of the visual cortex of human (20,34,35), monkey (8,17), and cat (36,37) reported an increase of response gain for small black targets but no change in response dynamics. Two possibilities might explain why our results on V1 dynamical states were not found in earlier experiments.…”
Section: Discussionmentioning
confidence: 99%